Productivity and biometric and physiological indices of sugarcane grown under different amounts of straw - Aquino, Gisele Silva de; Medina, Cristiane de Conti (Pesquisa Agropecuaria Brasileira, 2014)
The objective of this work was to evaluate the effect of different amounts of straw mulch on the biometric and physiological indices and on the yield of the sugarcane variety SP 801816, in the first crop cycle (plant cane). Five treatments – with 0, 25, 50, 75, and 100% straw mulch – were evaluated at 60, 180, 270, and 350 days after planting. The following biometric indices were determined: leaf area, number of leaves, fresh matter weight, and number of tillers. The physiological indices were: leaf area index (LAI), crop growth rate (CGR), and relative growth rate (RGR). A significant effect of straw mulch was observed on all variables. Treatments with 100, 75, and 50% straw provided the highest values for LAI, CGR, RGR, and number of tillers, and the treatments with 50 and 75% straw provided the highest yields. Keeping straw mulch at the soil surface had no effect detrimental to sugarcane development. Total removal or straw kept at 25% resulted in the lowest yields. Removal of 50% straw can be done without harming the crop.